2020
DOI: 10.21037/tcr.2019.12.65
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MTERF3 gene in breast carcinoma and the relationship with clinicopathological characteristics

Abstract: Background Mitochondrial transcription termination factor 3 (MTERF3) is a negative regulator of mitochondrial transcription. It is a modular factor involves in mitochondrial ribosome biogenesis and protein synthesis. However, the association between MTERF3 and breast cancers remains largely unknown. The aim of this study was to investigate the expression of MTERF3 in breast carcinoma and to analyze its clinicopathological significance, and to examine the potential prognostic value of MTERF3 in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…MTERF3, the most conserved member of mitochondrial transcription termination factor family, has been reported to negatively regulate the transcription of mitochondrial DNA (mtDNA) 13 . It has been reported that MTERF3 is upregulated in several cancers including breast cancer, brain glioma and colorectal cancer, and its high expression is correlated with poor outcomes in patients with those types of cancer [14][15][16] . However, the role of MTERF3 in HCC tumorigenesis remains elusive.…”
mentioning
confidence: 99%
“…MTERF3, the most conserved member of mitochondrial transcription termination factor family, has been reported to negatively regulate the transcription of mitochondrial DNA (mtDNA) 13 . It has been reported that MTERF3 is upregulated in several cancers including breast cancer, brain glioma and colorectal cancer, and its high expression is correlated with poor outcomes in patients with those types of cancer [14][15][16] . However, the role of MTERF3 in HCC tumorigenesis remains elusive.…”
mentioning
confidence: 99%